7-Chloro-4-[(E)-(3-chlorobenzylidene)hydrazinyl]-1λ4-quinolinium 3-chlorobenzoate - James L. Wardell; Edward R. T. Tiekink; R. Alan Howie; Marcus V. N. de Souza; Solange M. S. V. Wardell (Acta Crystallographica Section E, 2009)
The title salt, C16H12Cl2N3+·C7H4ClO2−, features a non-planar cation, the dihedral angle between the quinolinium and benzene residues being 18.98 (10)°. The cation adopts an E conformation about the C—N bond, and the amine group is oriented towards the quinolinium residue. In the crystal, N—H...O hydrogen bonds link two cations with two anions, forming a 20-membered {...OCO...HNC3NH}2 synthon. The dimeric units are connected into a linear supramolecular chain along [100] via π–π interactions [centroid–centroid distance = 3.5625 (13) Å].